Quality and Competitive Ability Evaluation Method Development Mobile Fleet - Ildarkhanov, Radik (Periodica Polytechnica Transportation Engineering, 2019)
The purpose of the article was to develop the evaluation method of mobile fleet. It is found that to evaluate production quality criterion of "integrated quality coefficient" is needed. Quality coefficient can be defined analytically. The author proposes the special formula to do this. Usage of analytical formula enables to conclude where one model excels the other, and where it is inferior. The formula validity check was performed. The research activities pursued by author enable to conclude that designed formula gives opportunity to evaluate product quality level objectively. Thus, competitive ability evaluation method resolves itself into choosing estimated product analogues and defining product quality coefficient using analytical method. Subsequently, prices and analogous product quality coordinates are put on two-coordinate field and dependency diagram of product price on its quality is built via least square method. Such method enables to evaluate quality and competitive ability of mobile fleet and make right choice.